Resursele de pe Internet ca ajutor în predarea la distanţă a limbii române ca limbă străină (Romanian Studies Today, 2024)
Based on my own pedagogical experience, I believe that in-person, face-to-face classes at university level cannot be fully replaced by distance learning courses, because emotional contact and real-life interaction between an instructor and students play a key role in acquiring knowledge. However, during the necessary distance learning period which has been lasting for more than a year (since the spring of 2020), the methods and learning tools of online education as well as their advantages have been crystallized. The article highlights some Internet resources (TV programmes, podcasts, publications, links, etc.) that may help to hold virtual classes of Romanian as a foreign language. These materials have been of great support in my practice of teaching the Romanian language online (with the help of programmes and platforms such as Zoom and Microsoft Teams) in the groups of Russian students in the first and in the third-forth year (bachelor's degree) who have been studying Romanian as their major specialization at St. Petersburg State University.
Keywords: Romanian as a foreign language; distance learning